Sustentabilidad económica en el taller de Cosechadoras Fortaleza Mecánica del cantón Babahoyo. - Yánez Cruz, Maritza Elizabeth (2022)
The present case study called Economic Sustainability in the Mechanical Fortress Harvesters Workshop of Babahoyo Canton, analyzes the economic sustainability of the Workshop and achieve the consolidation in the agricultural market in the elaboration of pieces and spare parts for the machineries, as well as offering new services to help maintain, the stability to the Workshop. The research methodology that was applied in the present this case study is the descriptive method, this analysis allowed all the information obtained, through the support of the execution of the research technique, what is the interview with the owner of the from Harvesters Workshop, through questions, with the finality of collect as much information as possible. The results generated through the application of information collection instruments in this investigative work allowed us to identify the main problematic that are evident with in the Mechanical Fortress Harvesters Workshop, is his income and expenses records it has shown that its current profitability only depends on the agricultural line, for this reason the Workshop is seeking to provide new innovative and updated services disposition to its clients frequent and future. These new services meet the proposed expectations, that is, the project in its functioning is a viable and attractive business.